Changes in community behavior post provision sanitation facilities in settlement area Padang Barat District - Vivi Handayani; Denny Helard; Yossyafra Yossyafra (The International Journal of Politics and Sociology Research, 2022)
West Padang sub-district is a sub-district that has tourism potential, because in this sub-district there is a tourist attraction Puruih beach or what is known as Padang beach. As a tourist area, this sub-district still has problems with the availability of toilets and inadequate sanitation, as well as the habits of the people who still use the coast as a place to defecate. This habit will certainly cause new health problems later if you continue to let it. In addition, there are also many people who do not have their own MCK at home, and are forced to use public MCK for bathing and defecating and urinating. However, currently there are very few public toilet facilities in this area and if they do exist they are in a dilapidated condition. Added to this is the behavior of the surrounding community who do not take care of the public MCK facilities that have previously been built. In this study, researchers wanted to see changes in people's behavior after sanitation facilities were built in their area. Are they going to maintain the facilities that have been provided or are they the same as before, let the facilities be abandoned as before.